The signal intensity of coronary culprit lesions on T1-weighted magnetic resonance imaging is directly correlated with the accumulation of vulnerable morphologies. (15th March 2017) - Matsumoto, Kenji; Ehara, Shoichi; Hasegawa, Takao; Nishimura, Satoshi; Shimada, Kenei
Abstract: Background: In the magnetic resonance T1-weighted imaging, some investigators have shown that coronary artery high-intensity signals (HISs) are associated with vulnerable plaque morphology and an increased risk of future cardiac events. Although previous studies used different PMR (the ratio between the signal intensities of coronary plaque and cardiac muscle) cutoff values to detect HIS, the association between PMR itself and plaque morphology has not been fully investigated. Methods and Results: We prospectively investigated the association between PMR values and plaque morphology detected by optical coherence tomography in consecutive 106 patients with angina pectoris. The lesions with almost all of the vulnerable features such as lipid-rich, thin-cap fibroatheroma, plaque rupture, thrombus, macrophage infiltrations, intimal vasculature, and absence of calcification had significantly higher PMR; the only exception was the presence of cholesterol crystals. PMR increases linearly with the number of vulnerable features (p < 0.0001, Rho = 0.504). Stepwise multiple linear regression analysis revealed that the absence of calcification (p = 0.0027), and the presence of thrombus (p = 0.0071) and intimal vasculature (p = 0.019) were independently associated with higher log-transformed PMR. There was a stepwise increase in PMR of the culprit lesions in proportion to the accumulation of the number of adverse plaque characteristics defined as non-calcified plaque, thrombus, and/or intimal vasculature. Conclusion: These results suggest that not only the presence of HIS, but also the elevated PMR itself may be used as a quantitative marker of plaque vulnerability in clinical evaluation. Highlights: High-intensity signals on T1-weighted imaging relate to coronary vulnerable plaque morphology. The ratio between the signal intensities of coronary plaque and cardiac muscle (PMR) is proposed. PMR increases linearly with the number of vulnerable features on optical coherence tomography.